Gramsci y el factor religioso: su relación con la Teología de la Liberación Latinoamericana = Gramsci and the religious factor : its relationship with Latin American Liberation Theology - Paganelli, Pía (Ciencias sociales y religión, 2016)
The Liberation Theology in Latin America complements Marxism in the configuration and pedagogic dissemination of a new anti-capitalist culture. At the same time, considered as a popular cultural movement, it has also an emancipator function such as AntonioGramsci establishes for the Communist Party: Ideological stimulation towards socialism, critic of the capitalist system, stimulation towards revolutionary organizations, and ideological legitimation of a revolutionary project. Given this analogy, the present article tends to analyze Gramsci’s vision over the religious element, and its similarities with the project of the Liberation Theology, both of which defend the dialogue between Christians and Marxists.